Micro- and nanoformulations of paclitaxel based on micelles, liposomes, cubosomes, and lipid nanoparticles: Recent advances and challenges. Issue 2 (February 2022) - Alavi, Mehran; Nokhodchi, Ali
Graphical abstract: Highlights: Active targeting to reduce cytotoxicity of paclitaxel towards healthy cells. The amount of paclitaxel for incorporation in the bilayer of liposome is limited. Paclitaxel loading in core and bilayer sections of liposome shows sustained release. Surface functionalization of micelle, liposome, and cubosome should be considered. Abstract: The diterpenoid molecule paclitaxel (PTX), extracted from the Western yew tree, Taxus brevifolia, is a promising anticancer drug specifically in clinical use for ovarian and breast cancers. However, its wider use is hampered by adverse effects and emerging resistance in cancer cells. Micelles, liposomes, cubosomes, and lipid nanoparticles (LNPs) have the potential to reduce or even remove complications associated with the use of PTX. Herein, we provide an overview of micro- and nanoformulations of PTX based on micelles, liposomes, cubosomes and LNPs to improve the therapeutic effects of this drug both in vitro and in vivo.